An imidazole based colorimetric sensor for fluoride anion - Goswami, Shyamaprosad; Chakrabarty, Rinku (European Journal of Chemistry, 2011)
Nine 2,3,5-triphenylimidazole derivatives having nitro and/or OH groups at their phenyl groups as receptors have been designed and synthesized for the colorimetric detection of F- ion, among which receptor (1) having a nitro group at the para position of the 2-phenyl group with respect to the imidazole moiety shows colorimetric responses (yellow to red) in acetonitrile-water (9:1, v:v) mixture towards F- anion selectively among other anions studied. Here nitro group acts as a signaling unit and OH and NH of imidazole moieties act as binding sites respectively.